2012
DOI: 10.1016/j.conbuildmat.2012.04.066
|View full text |Cite
|
Sign up to set email alerts
|

An overview on concrete carbonation in the context of eco-efficient construction: Evaluation, use of SCMs and/or RAC

Abstract: h i g h l i g h t s " This paper reviews current knowledge on concrete carbonation when SCMs and/or RAC are used. " The use of the phenolphthalein indicator underestimate real concrete carbonation by as much as 100%. " The use of SCMs and and/or RAC increase the carbonation depth unless low w/b is used. " The most relevant factors that influence concrete carbonation are analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(52 citation statements)
references
References 69 publications
(81 reference statements)
0
50
0
2
Order By: Relevance
“…The relative humidity (RH) and the concentration of CO2 are the most important environmental factors (Aguirre and Mejía de Gutiérrez, 2013). It has been reported that RH values between 50% and 75% promote the diffusion of CO2 (Roberts, 1981) and that CO2 concentration in the atmosphere may fluctuate from 0.03% in rural environments to over 0.3% in cities, where the incidence of carbonation is higher (Gruyaert et al, 2013;Pacheco-Torgal, 2012). For this reason, in tropical non-marine environments carbonation may be the main deterioration mechanism in reinforced concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The relative humidity (RH) and the concentration of CO2 are the most important environmental factors (Aguirre and Mejía de Gutiérrez, 2013). It has been reported that RH values between 50% and 75% promote the diffusion of CO2 (Roberts, 1981) and that CO2 concentration in the atmosphere may fluctuate from 0.03% in rural environments to over 0.3% in cities, where the incidence of carbonation is higher (Gruyaert et al, 2013;Pacheco-Torgal, 2012). For this reason, in tropical non-marine environments carbonation may be the main deterioration mechanism in reinforced concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The publications identified under this category were sorted into two groups based on their origins -firstly, technical reports produced from established organisations mainly in Europe and North America and one in Asia and, secondly, review papers originating from individual researchers (Ayub et al, 2013;Bertolini et al, 2013; Hamada, 1968;Jain et al, 2007;Nagataki et al, 1989;Pacheco Torgal et al, 2012;Richardson et al, 2012;Sakai et al, 2012;Sanjuan et al, 2011;Siddique, 2008;Siddique and Khan, 2011;Song and Saraswathy, 2006). The main observations from the former group are summarised in Table 1.…”
Section: Technical Reports and Review Papersmentioning
confidence: 99%
“…Pero esta protección puede fallar, debido por ejemplo a la acción del CO 2 , reduciendo la alcalinidad debido a la carbonatación (Song y Saraswathy, 2007). Esta reacción depende fundamentalmente de la humedad relativa ambiente, la temperatura, la permeabilidad del concreto y la concentración de CO 2 (ACI 201.2R-01, 2000;Pacheco et al, 2012).…”
Section: Introductionunclassified